Examining the role of store design on consumers' cross-sectional perceptions of retail brand loyalty. (September 2017) - Murray, John; Elms, Jonathan; Teller, Christoph
Abstract: This paper compares new and established store design prototypes of the same retailer to examine the role of consumers' cross-sectional perceptions of retail brand loyalty. In-store surveys were administered to capture consumers' store-level perceptions towards a new store prototype and an older established prototype of the same fast fashion retailer. The data was subjected to multi-group analyzes with structural equations modeling. The findings suggest that store novelty and complexity promote both store design pleasure and retail brand loyalty outcomes. The different store designs do not, however, account for differences in brand loyalty perceptions at the overall retailer level when multi-group comparisons of both store designs are made. Consumers of newer store designs are found to possess a heightened sensitivity to price perceptions. Managerial implications of the effects of store novelty and complexity on retail brand loyalty are also presented.